The Influence of Social Media Marketing and Electronic Word of Mouth on Interest in Choosing Dhyana Pura University, Bali Through Brand Image Mediation - Pratama, I Gede Ngurah Wira; Adinegara, Gusti Ngurah Joko; Komalasari, Yeyen; Santoso, R Tri Priyono Budi (The Eastasouth Management and Business, 2024)
This study examines the influence of Social Media Marketing (SMM) and Electronic Word of Mouth (eWOM) on the level of interest in selecting Dhyana Pura University Bali, with brand image serving as a mediator. Utilizing a quantitative research approach, data was gathered from students at the university and analyzed through SEM-PLS. The results highlight that both SMM and eWOM significantly enhance the university's brand image, which in turn positively affects students' interest in choosing the institution. The findings suggest that effective utilization of SMM and eWOM can be crucial strategies for educational institutions aiming to enhance their attractiveness and competitive edge in the educational sector.